Hypothermic Perfusion Effects on Corneal Endothelial after Phacoemulsification - Afia Nuzila Fadhlina (Journal of Medicine and Health Technology, 2026)
Phacoemulsification is the most common cataract surgery performed as an efficient and safe cataract surgery technique compared to other cataract surgery techniques. Indeed, phacoemulsification uses high-intensity ultrasound energy to fragment and emulsify the lens, which can cause trauma to the cornea, especially the endothelial layer. Surgical trauma to the CEC can have severe complications on functional outcomes such as decompensation, leading to corneal edema with visual impairment and irreversible bullous keratopathy. The application of hypothermia is known to have a protective effect on various cells and tissues, so hypothermia perfusion is considered to protect the corneal endothelium during phacoemulsification procedures. Hypothermic perfusion can be used to reduce corneal endothelial cell damage during phacoemulsification procedures.